Model Matematika Penyebaran Penyakit Bakteri Pumbuluh Kayu Cengkeh (BPKC) - Chijra; Hajar; Ratianingsih, R (Program Studi Matematika, Universitas Tadulako, 2019)
ABSTRACTClove wood vessels is one of the most damaging diseases of clove plants. This disease is caused by the bacterial Ralstonia Syzygii. the bacterial Rasltonia Syzygii lives in clove wood vessels. The bacterial Ralstonia Syzygii ispread through the Hindola Spp vector. The matemathical model that represents the spread of the disease isdeveloped from the SEI model (Suspectible, Exposed, Infected). The model gives 4 critical points ð‘‡1, ð‘‡2, ð‘‡3 and ð‘‡4 exist interaction between bacterial population Ralstonia Syzygii and Hindola Spp vector is less than the level of vulnerable clove recruitman divided by carrying capacity of Ralstonia Syzygii bacterial multiplied by Hindola Spp carrying capacity. The results of system stability analysis at the critical point using linearization give unstable three critical points ð‘‡1, ð‘‡2, ð‘‡3which describes equilibrium conditions and a stable ð‘‡4 critical point which describes endemic conditions. Numerical simulations are carried out to describe temporary disease-free conditions, and stable endemic conditionsKeywords : Clove Wood vessel Disease, Linierization Method, SEI Model